A Novel 3D Point Cloud Reconstruction Method for Single-Pass Circular SAR Based on Inverse Mapping with Target Contour Constraints - Qiming Zhang; Jinping Sun; Fei Teng; Yun Lin; Wen Hong (Remote Sensing)
Circular synthetic aperture radar (CSAR) is an advanced imaging mechanism with three-dimensional (3D) imaging capability, enabling the acquisition of omnidirectional scattering information for observation regions. The existing 3D point cloud reconstruction method for single-pass CSAR is capable of obtaining the 3D scattering points for targets by inversely mapping the projection points in multi-aspect sub-aperture images and subsequently voting on the scattering candidates. However, due to the influence of non-target background points in multi-aspect sub-aperture images, there are several false points in the 3D reconstruction result, which affect the quality of the produced 3D point cloud. In this paper, we propose a novel 3D point cloud reconstruction method for single-pass CSAR based on inverse mapping with target contour constraints. The proposed method can constrain the range and height of inverse mapping by extracting the contour information of targets from multi-aspect sub-aperture CSAR images, which contributes to improving the reconstruction quality of 3D point clouds for targets. The performance of the proposed method was verified based on X-band CSAR measured data sets.